Որոշ եզրահանգումներ ԱԼԵՔՍԱՆԴՐ ՀԱՐՈՒԹՅՈՒՆՅԱՆԻ ստեղծագործության շուրջ - Պետրոսի Զուրաբյան Ժաննա (Musical Armenia, 2011)
Review analytical article of P.h.D candidate, Professor of Yerevan State Conservatory after Komitas, Janna P. Zurabyan "The composer’s jubilee: thoughts of creative individuality" is dedicated to the creative work of Nation artist of USSR, composer Alexander G. Harutyunyan. The author considers the composer’s works from the genre viewpoint, his primacy in several Armenian composing arts.